A new Australian species of Eotetranychus (Acari: Tetranychidae) from buck spinifex Triodia mitchelli (Poaceae), intraspecific variation in Eotetranychus, and the synonymy of Platytetranychus with Eotetranychus - Seeman, Owen D.; Beard, Jennifer J.; Zhang, Lanni (Zootaxa, 2017)
Eotetranychus spinophilus sp. nov. is described from adults and deutonymphs collected from the spinifex grass Triodia mitchelli (Poaceae) in Queensland, Australia. The species Eotetranychus sexmaculatus (Riley, 1890) is considered absent from Australia; all previous records are instead Eotetranychus queenslandicus Manson, 1967. A key to the six Australian species of Eotetranychus Oudemans, 1931 is provided. Although our new species is classified in Eotetranychus, it also resembles some species of Schizotetranychus Trägårdh, 1915. We reaffirm previous suggestions of polyphyly within Schizotetranychus and observed that the patterns of leg striae (e.g. longitudinal striae on tibiae and tarsi III–IV) may have taxonomic value within Schizotetranychus, but that such patterns are rarely included in descriptions of spider mites. We also discuss the relationships between Eotetranychus and the closely related genera Mononychellus Wainstein, 1971, Palmanychus Baker & Tuttle, 1972 and Platytetranychus Oudemans, 1931. We show that the type species of Platytetranychus, P. gibbosus Canestrini, 1889, is an incertae sedis taxon that is not a member of the Tetranychini, and for this and other reasons, we synonymise Platytetranychus with Eotetranychus.                                                                                                                          Leg setation is reported for all six Australian species and three European species of Eotetranychus. Although each species has a characteristic leg setation, variation is common, with 51% of specimens having at least one anomaly. Asymmetrical setal losses accounted for most variation (43% of specimens), but in five specimens (9%) the loss was symmetrical. Variation in the expression of setae was found mostly in setae added in the adult (21/27 variable setae), representing about two-thirds of the total 33 adult leg setae added in Eotetranychus. We therefore stress the need for multiple specimens when describing a new species, especially if species are being separated using differences in leg setation, and particularly those setae that are added in the adult life stage.